(untitled) (Advancements in Homeopathic Research, 2022)
Background & Objectives: Objective: To study about the prevalence of hypothyroidism in the age of 15- 55 years. To study the efficacy of homoeopathic constitutional treatment in Hypothyroidism.Hypothyroidism is now a days prevailing in both sexes. It has long been recognized that thyroid dysfunction may have profound effects on the female reproductive system. Thyroid disorders are 10 times more common in women than in men. Majority of the cases of subclinical hypothyroidism easily pass unrecognized. The prevalence of subclinical hypothyroidism is as high as 9.5 percent in women.